Pilot of integrated, colocated neurology in a primary care medical home. Issue 3 (12th December 2016) - Young, Nathan P.; Elrashidi, Muhamad Y.; Crane, Sarah J.; Ebbert, Jon O.
Abstract: Rationale, aims, and objectives: Novel health care delivery models are needed to reduce health care use while delivering effective and safe care. We developed a model of a neurologist integrated and colocated in primary care leveraging "curbside, " electronic, and traditional consultations. Our objective was to examine the impact on health care resource use of diagnostic testing and referrals for face‐to‐face neurological consultation and adverse outcomes associated with electronic and curbside consultations. Methods: Consecutive patients from December 1, 2014, to March 13, 2015, were included in the analysis about whom contact was made between a primary care clinician and a colocated neurologist. Results: Over 3.5 months of the pilot, 359 unique patients generated 429 consultations (179 curbsides, 68 electronic consultations, and 182 face‐to‐face visits). The integrated model resulted in avoidance of 78 face‐to‐face tertiary neurology consultations, 39 brain magnetic resonance imaging, 50 electromyograms, and 53 other advanced imaging studies. Earlier curbside consultation may have prevented unnecessary testing or face‐to‐face tertiary neurology consultations in 40 (22%) patients. Earlier face‐to‐face consultation may have avoided expensive testing in 31 (17%) patients. No cases met criteria for an adverse outcome. The number of referrals to tertiary neurology declined by 64%, and the total number of face‐to‐face visits per month declined by 25%. Conclusion: Colocated neurology in a primary care medical home offers a promising intervention to deliver high‐value care.